A Spatial Analysis of Happiness - Aral, Neşe; Bakır, Hasan (Panoeconomicus, 2024)
In this study, the differences in the spatial pattern of happiness will be revealed and the distribution of the relationship between happiness and economic variables between countries will be discussed. When the distribution pattern is examined, it can be observed that happy and unhappy countries are concentrated in certain areas. Therefore, the concept of happiness has been evaluated from a geographical point of view. From the analysis of 147 countries in this study, it was found that economic freedom and GDP have a positive effect on happiness whereas inflation and unemployment have a negative effect. A striking result was that in addition to the relevant economic variables, location is also effective in the interpretation of happiness. One of the significant results of the study was that geography is a factor to consider in investigating the relationship between economic variables and happiness. JEL: C21.